Growing Up Queer : Kids and the Remaking of LGBTQ Identity - Robertson, Mary Anna (Book collections on Project MUSE., 2019)
'Growing Up Queer' explores what it is like being young and lesbian, gay, bisexual, transgender, and/or queer (LGBTQ) in the United States today. Using interviews and ethnographic research conducted at an LGBTQ youth drop-in centre, it shows how young people understand their sexual and gender identities, their interest in queer media, and the role that family plays in their lives. The young people who participated in this research are among the first generation to embrace queer identities as kids and teens, and this text shows how both sexual and gender identities are formed through complicated, ambivalent processes, as opposed to the natural characteristics one is born with.